Genetic Variability Study of Local Rice Genotypes - Panth, P.; Dahal, A.; Upadhyay, K. (Journal of Agriculture and Environment, 2021)
Rice is a self- pollinating, major staple food crop growing in tropical and having high importance in food security and economy of the country. The study was conducted main season during first week of May to third week of September 2018 in the research field of Gokuleshwor Agriculture and Animal Science College, Baitadi of Sudurpaschim province in 3 replications in Randomized Complete Block Design with 13 local genotypes including 2 improved checks Black rice (G-60) and Sukkha Dhan-3 to evaluate performance of different local rice varieties grown in Gokuleshwor agro-environment. Phenotypic traits like plant height, tiller number, panicle number, panicle length, leaf area index and genotypic traits like thousands kernel weight, grain/panicle, productivity, biological yield and harvest index were the traits evaluated Highest grain yielding genotype was Naka Dhan (7.80ton/ha) and highest thousands kernel weight was found in Chiude (30.33 gm) . Phenotypic coefficient of variation was highest for number of unfilled grains per spike (81.39) followed by leaf area (51.37 cm2) and lowest magnitude was exhibited by number of spike/panicle (26.16) and harvest index (19.44%). The heritability was highest for thousands kernel weight (99.07%) followed by plant height (95.23%) and panicle length (76.34%) and lowest for unfilled grains/spike (41.69%) and yield (41.36%). Correlation study suggested that productivity showed the positive significant association with biological yield (0.896) and harvest index (0.348). Most of other traits have shown positive association with productivity. Thus, Chiude and Naka dhan genotypes could further be used for breeding programmes for the environmental condition of Baitadi district, Nepal.